Analisis Postur Kerja untuk Mengurangi Risiko MSDs dengan Metode REBA di PT Maju Mapan Bahagia Sidoarjo - Dhifa Farah Miftah; Akmal Suryadi (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Musculoskeletal Disorder (MSDs) are work-related health disorders that are often experienced by workers. PT. Maju Mapan Bahagia is a manufacturing company engaged in food processing. Production workers do not apply ergonomic work postures in carrying out their work activities, this causes workers to experience a number of complaints such as complaining of pain in the neck, back, shoulders, arms and calves. This research was conducted to determine the level of potential risk of MSDs in production workers using the methodRapid Entire Body Assessment (REBA) and provide suggestions for better working postures. The REBA method is a method used to measure and analyze workers' body posture. Based on the results of body posture analysis using the REBA method, workers in the frozen meat breaking process scored 6, which means the risk level is moderate and corrective action is needed, workers in the meat grinding and cooking process got a score of 11, which means the risk level is very high and corrective action is needed as soon as possible, while workers in the cooling process received a score of 8, which means the risk level is high and immediate corrective action is needed. Proposed improvements to reduce complaintsmusculoskeletal disorders is by improving the posture of the neck, back, arms, wrists, grip and legs and providing facilities in the form of wooden pallets, higher tables and jigsaw machines.